2004
DOI: 10.1158/0008-5472.can-04-2077
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin-Mediated Apoptosis Is Regulated by Adenomatous Polyposis Coli and Is p21 Dependent but p53 Independent

Abstract: Clusterin is a widely expressed glycoprotein that has been paradoxically observed to have both pro-and antiapoptotic functions. Recent reports suggest this apparent dichotomy of function may be related to two different isoforms, one secreted and cytoplasmic, the other nuclear. To clarify the functional role of clusterin in regulating apoptosis, we examined its expression in human colon cancer tissues and in human colon cancer cell lines. We additionally explored its expression and activity using models of aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…Although some reports have indicated CLU to be up-regulated in neoplastic colorectal tissues (7,15), others have indicated down-regulation (16). This apparent discrepancy is not unique for studies investigating CLU expression in CRC as it has also been reported for prostate cancer (1).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although some reports have indicated CLU to be up-regulated in neoplastic colorectal tissues (7,15), others have indicated down-regulation (16). This apparent discrepancy is not unique for studies investigating CLU expression in CRC as it has also been reported for prostate cancer (1).…”
Section: Discussionmentioning
confidence: 97%
“…However, previous studies on CLU expression in CRC have disagreed on whether CLU is up-regulated (7,15) or downregulated by the cancer cells (16). There are many possible explanations for the inconsistent observations, e.g.…”
mentioning
confidence: 97%
“…following the extended fast, is increased in parallel with increased CDKN1A in response to oxidative and other cellular stresses (Han et al 2008) and in liver following treatment with glucocorticoids; hormones that help to regulate blood glucose during fasting (Wong et al 2010). Expression of clusterin at the level of mRNA is, at least in part, dependent on CDKN1A (Chen et al 2004). Clusterin, for which the mRNA levels increased following the extended fast, is a regulator of apoptosis and its expression is used as a marker of cell senescence (Petropoulou et al 2001;Trougakos et al 2006).…”
Section: Effects Of Extended Fast On Pbmc Transcription Profilesmentioning
confidence: 99%
“…Moreover, we also found that CLU expression is down-regulated during prostate cancer progression in the TRAMP mouse model . When overexpressed, CLU causes growth inhibition and death of prostate cell lines, as a consequence of nuclear accumulation (Caccamo et al, 2003(Caccamo et al, , 2005Chen et al, 2004). One of the possible explanations for the contrasting biological effects of CLU in different settings is that it can shuttle between the outside and inside the cell.…”
Section: Introductionmentioning
confidence: 99%